2021
DOI: 10.1002/smtd.202100725
|View full text |Cite
|
Sign up to set email alerts
|

Defects in CsPbX3 Perovskite: From Understanding to Effective Manipulation for High‐Performance Solar Cells

Abstract: Figure 10. a) Rotational distortion of [BX 6 ] 4− ([PbX 6 ] 4− ) octahedra by introducing smaller B-site cations. Reproduced with permission. [176] Copyright 2018, American Chemical Society. b) Schematic of the formation and stability of α-CsPbI3, γ-CsPbI 3 , and Ca 2+ -doped γ-CsPbI 3 . Reproduced with permission. [144] Copyright 2019, Wiley-VCH. c) The Mn 2+ doping modes by either forming a substitution or an intersitial. Reproduced with permission. [145] Copyright 2018, American Chemical Society. d) Energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 204 publications
1
39
0
Order By: Relevance
“…However, the ligands cannot completely passivate all of the dangling bonds presented by atoms at the nanocrystal surface because of the steric hindrance between neighboring alkyl chains . It is known that water can interact with surface defects on the surface of lead halide perovskites and induce halide vacancies. Liu et al showed that oxygen can passivate halide vacancies in CsPbI 2 Br and speculated that a decrease in exposed halide vacancies limits the adsorption of water. It is possible that both halide vacancies and water adsorption are involved in the formation of slow surface trap states on γ-CsPbI 3 nanocrystals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ligands cannot completely passivate all of the dangling bonds presented by atoms at the nanocrystal surface because of the steric hindrance between neighboring alkyl chains . It is known that water can interact with surface defects on the surface of lead halide perovskites and induce halide vacancies. Liu et al showed that oxygen can passivate halide vacancies in CsPbI 2 Br and speculated that a decrease in exposed halide vacancies limits the adsorption of water. It is possible that both halide vacancies and water adsorption are involved in the formation of slow surface trap states on γ-CsPbI 3 nanocrystals.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the inorganic perovskite film always contains a high density of defects, which leads to serious charge recombination and hence reduced steady-state carrier density throughout the film bulk. [14][15][16] To optimize the crystallization of inorganic perovskite as well as efficiently passivate the defects, a variety of organics have been introduced into the perovskite precursor solutions. The resulting organics-doped inorganic perovskites usually exhibited greatly improved photovoltaic performance relative to pristine ones.…”
Section: Introductionmentioning
confidence: 99%
“…In CsPbX 3 PSCs, the most harmful defects are mainly distributed at the grain boundaries and interfaces. 16 Inspired by the concept of surface passivation in Si technology, various organic/inorganic agents have been employed to heal the perovskite surface. However, the insulating or weakly conductive character of these passivators hinders the charge carrier transport.…”
Section: Introductionmentioning
confidence: 99%